Collections as data: Computational access to digital collections - Candela, Gustavo (Anuario ThinkEPI, 2024)
During the last years, Cultural Heritage institutions have been exploring new ways to make available their digital collections. Collections as data is an initiative that fosters the publication of digital collections suitable for computational use. The research community has made available best practice and examples of projects to facilitate the adoption of the Collections as Data principles. This work presents the initiative Collections as data and introduces relevant projects based on Cultural Heritage institutions, best practice and new challenges.